The lacemaker's secret : a Chloe Ellefson mystery - Ernst, Kathleen, 1959- (A Chloe Ellefson mystery, 2018)
Chloe discovers a body on a farm outside Green Bay while she's visiting a historic site and conferring with a friend about Belgian lacemaking.